"A Country Proud to be Democratic": Demanding Democracy in Nineteenth-Century Chile. Issue 4 (October 2019) - Edwards, Lisa M.
Abstract: This article examines criminal court cases about conflicts related to the electoral process at all stages from determining how elections would be administered to disputes about results. It argues that contemporary allegations of fraud, corruption, and misconduct during elections can inform us not only of the anomalies but also of the ways in which elections worked as expected, according to the laws and norms of the time. We can also see how participants defined and defended the democratic ideal. A careful reading of participants' complaints to local authorities about electoral law violations, including incidents that ended in violence, can provide important insights into partisanship, the mechanics of elections, and the formation of political culture. The use of democratic rhetoric in these complaints suggests a consensus around a democratic ideal based on free and fair elections even though that ideal was not yet realized. Through the analysis of criminal court cases, it also introduces a broad range of questions about how nineteenth-century Chileans understood and practiced democracy that suggest avenues for further research.